Gut microbiota and dietary intervention: affecting immunotherapy efficacy in non–small cell lung cancer - Xin, Yu; Liu, Chen-Guang; Zang, Dan; Chen, Jun (Frontiers in Immunology, 2024)
Nonsmall cell lung cancer (NSCLC) accounts for 80 -85% of all lung cancers. In recent years, treatment with immune checkpoint inhibitors (ICIs) has gradually improved the survival rate of patients with NSCLC, especially those in the advanced stages. ICIs can block the tolerance pathways that are overexpressed by tumor cells and maintain the protective activity of immune system components against cancer cells. Emerging clinical evidence suggests that gut microbiota may modulate responses to ICIs treatment, possibly holding a key role in tumor immune surveillance and the efficacy of ICIs. Studies have also shown that diet can influence the abundance of gut microbiota in humans, therefore, dietary interventions and the adjustment of the gut microbiota is a novel and promising treatment strategy for adjunctive cancer therapy. This review comprehensively summarizes the effects of gut microbiota, antibiotics (ATBs), and dietary intervention on the efficacy of immunotherapy in NSCLC, with the aim of informing the development of novel strategies in NSCLC immunotherapy.